Social Innovation in Character Learning: Supporting of Primary School Achievement - Wijayanti, Okto; Wiarsih, Cicih; Dwiningrum, Siti Irene Astuti (LPPM Undiksha, 2021)
Research focuses on the process of social innovation, innovative ideas, changes in character for the better, the involvement of the principal in innovation, and forms of innovation to support school achievement on a micro level. Positive things related to school innovation can be recommendations for other primary schools. to support the achievement and quality of primary schools. This research uses descriptive qualitative method with a case study approach. The informants in this study were principals and teachers, students and social school innovation leaders. The research data collection technique uses an empirical approach, observes, records data from interviews and studies documentation in this case. The importance of social innovation connects ideas for problem solving with problem solutions to find change, making students, teachers and school members excited to learn and work in dynamic and fun school conditions. Social innovation provides inspiration, stimulates creativity, comfort and conduciveness. The involvement of the principal as a role model, providing empathy, innovators and motivators realizes the importance of providing stimulation and being a motivator so that social school innovation in character learning can be implemented so that it can support school achievement with the synergy of all school and community parties. The leadership of the principal shows a complex understanding of organizational learning so that it can bring about change as a guide for implementing school innovation effectively and sustainably.